Franks, locals and sugar cane: a case study of cultural interaction in the Latin Kingdom of Jerusalem. Issue 3 (27th May 2019) - Bronstein, Judith; Stern, Edna J.; Yehuda, Elisabeth
ABSTRACT: This study examines influences and cultural interactions between Frankish settlers and the local populations in the Latin kingdom of Jerusalem through the prism of sugar cane, a local food crop unfamiliar to many crusaders and Latin settlers. Combining textual and archaeological evidence for sugar cane cultivation, production and consumption, the article explores the extent to which the Latin population – a numerical minority and the ruling elite – was influenced by and influenced their new environment and the local inhabitants. It focuses on sites near Acre for which there is historical and archaeological evidence of sugar production from before the arrival of the crusaders, and during Frankish period (twelfth and thirteenth centuries). After acquainting themselves with the new land and its products, the Franks became largely involved in the production of sugar, one of the kingdom's most lucrative cash-crops, which brought significant technological developments and changes in the lives of local inhabitants.